A rare case of mediastinal pseudocyst in patient after acute pancreatitis - Koželský, P; Hoskovec, D; Ulrych, J; Krška, Z (Rozhledy v chirurgii, 2025)
Acute pancreatitis may present with a variety of complications, the whole range of thoracic complications is presented as the rare enzymatic ascending mediastinitis as well as rare mediastinal pseudocysts. The mortality rate of mediastinal complications is high, 14-47%. Due to the small number of described cases, no clear recommendations have been made regarding the treatment of mediastinal pseudocyst. From the documented cases, spontaneous regression of mediastinal pseudocysts is rare and the clear benefit is reached by endoscopic treatment. Surgical therapy should be indicated only in case of failure of pharmacotherapy or endoscopic treatment. The differential diagnosis of the patient's difficulties after pancreatitis includes a whole range of polymorphic manifestations. However, as we illustrate in this case report, we should not forget them, especially because of the mortality rate.
Keywords: Pancreatitis; Mediastinitis; mediastinitida; acute panctreatitis; Middle Aged; mužské pohlaví; Pancreatic Pseudocyst; pankreatická pseudocysta; mediastinal pseudocysts; case report; acute pancreatits; Humans; Mediastinal Cyst; Acute Disease; lidé středního věku; cysty mediastina; akutní nemoc; pankreatitida; lidé; Male